Behavior of hot-cast anchor sockets for prestressed cable structures under fire. (April 2023) - Hang, YANG; Mei-chun, ZHU; Fan-qin, MENG
Abstract: Zn-Cu alloy filled hot cast anchor sockets are the main link in prestressed cable systems, which could be a significant safety issue without appropriate structural fire design. Thus, two full-scale specimens were heated and loaded until failure to assess the fire performance of the sockets herein.Experimental results show that the temperature of Zn-Cu alloy filler decreases gradually from the bottom to the top along the central axis of sockets, thus Zn-Cu alloy at the bottom of the sockets will melt first.The whole slip process of hot-cast anchor under fire comprises three stages as non-slip, stable growth and sharp acceleration.In the test, the critical temperature of the hot-cast anchors is 374 °C – 387 °C, and conservatively taken as 350 °C. Then, a numerical model was developed and validated through general finite element software ABAQUS, through which the effects of the heating curves, specimen dimensions and steel wire bundle types on fire resistance are further explored. The simulation results reveal that the heating curves and specimen dimensions have significant influence on fire resistance of the specimens, whereas the effect of steel wire bundle types can be neglected. Compared with other heating curves, changing the dimensions has the most obvious effect on the fire resistance of the specimen under the action of HC heating curve.